التنبؤ بالهطل المطري في محطة طرطوس الواقعة في القسم الجنوبي من الساحل السوري - حايك, شريف بدر; عمّار, غطفان عبد الكريم (Latakia University Journal -Engineering Sciences Series, 2016)
يعدّ الهطل المطري أحد أكثر عناصر الدورة الهيدرولوجية صعوبة وتعقيداً من حيث الفهم والنمذجة، بسبب تعقيد العمليات الجوية التي تولد الأمطار. تأتي أهمية البحث من العلاقة المباشرة لكميات الأمطار الهاطلة بالأنشطة الاقتصادية والاجتماعية للسكان، ومجالات التخطيط لإدارة الموارد المائية، لا سيما ما يتعلق منها بعملية التنمية الزراعية. يهدف البحث إلى إلقاء الضوء على كميات الأمطار الهاطلة في محطة طرطوس الواقعة في الجزء الجنوبي من الساحل السوري، وتطبيق نموذج من نماذج بوكس-جنكنز للتنبؤ بكمياتها المستقبلية. تم اختبار نماذج متعددة لـ ARIMA، وأخضعت النماذج لجميع الاختبارات المطلوبة، وقد تبين أن أفضلها كان النموذج ذي المعالم ARIMA(3,0,4). جرى أثناء الاختبار تقسيم البيانات إلى 43 سنة لبناء النموذج، وثماني سنوات لاختباره، وقد أعطت نتائج الاختبار دقةً عاليةً في الأداء، كما استخدم النموذج للتنبؤ بقيم الأمطار السنوية لعشرين سنة قادمة.Rainfall is considered as one of the most difficult and complex elements of the hydrological cycle, to understand and model, due to the complexity of air operations that generate rain. The importance of research comes from the direct relationship between the rainfall amount and economic & social activities of the population, planning scopes of the water resources management, particularly with respect to the agricultural development. The research aims to highlight the rainfall amounts in Tartous station which is located in the southern part of the Syrian coast, and applying one model of Box-Jenkins models for the purpose of predicting future rainfall amounts. Multiple Arima models have been tested. The results showed that the model SARIMA (3,0,4) was the best one. Data were divided into 43 years to build the model and eight years to test it. The test results gave high accuracy in the performance, and the model was used to predict the values of annual rainfall for the next twenty years.